Fatigue characteristics and mechanism of phosphogypsum stabilised red clay under dry and wet cycles - Yan Hu; Kaisheng Chen; Yuang Chen; Jinxiong Chen; Kai Zhang (PLoS ONE, 2025)
Phosphogypsum is an acidic solid waste mainly composed of CaSO₄-2H₂O by-products of the wet process phosphoric acid industry, which has the characteristics of high impurity content, poor stability of stockpiling, but can be utilized in a resourceful way. Phosphogypsum waste utilization can reduce environmental pollution, save resources and create economic value. In order to investigate the fatigue characteristics and the mechanism of dynamic strength change of cement-phosphogypsum-red clay under wet and dry cycles, the cumulative deformation characteristics and the rule of change of critical dynamic stress of the mixed materials were investigated by dynamic triaxial fatigue test, SEM and XRD test, and the mechanism of dynamic strength change was analyzed according to the microstructure and the chemical mineral composition of the mixed materials. The test results show that: the cumulative deformation curve of the mix under the action of dry and wet cycles is divided into three types: stable, destructive and critical, and the critical dynamic stress is positively related to the peripheral pressure and consolidation ratio, and negatively related to the number of dry and wet cycles; the mechanism of dynamic strength change: the hydration of cement generates hydrated calcium silicate gel, which coalesces fine particles of the mix to form agglomeration, and the calcium sulfate dihydrate in phosphogypsum reacts with it to generate calcium alumina, and at the same time, the particles form clusters through electrostatic adsorption, and the particles of calcium sulfate dihydrate react with it to form calcium alumina. Through electrostatic adsorption to form clusters, a variety of agglomerates intertwined to form a stable structure with a certain strength. Relative to other proportions of phosphogypsum and red clay, the mix has better dynamic strength at a 1:1 mass ratio of phosphogypsum to red clay; and too much phosphogypsum will make the mix acidic increase, resulting in some of the calcium alumina dissolved, while the dry and wet cycle will increase the internal pores of the mix, reducing the strength of the mixture.